La ejecución inmediata de las sanciones disciplinarias impuestas en el marco del régimen disciplinario del servicio civil como afectación del derecho al trabajo - Acuña Oscco, Diana Carolina (2024)
With the entry into force of the disciplinary regime contemplated in Law No. 30057, Civil Service Law, its General Regulations, approved by Legislative Decree No. 040-2014-PCM and the guidelines set forth in Directive No. 02-2015-SERVIR/GPGSC, a single disciplinary regime applicable to all civil servants has been established. Upon the commission of a disciplinary administrative offense by a civil servant, such regime has provided for the imposition of a sanction, after a disciplinary administrative procedure, which according to Article 88 of the Civil Service Law may be a written reprimand, suspension without pay from one day to twelve months or dismissal (which brings with it the accessory sanction of disqualification). Now, article 95 of Law No. 30057, in accordance with Articles 116 and 117 of its Regulations, provides that disciplinary sanctions are effective as of the day following their notification and that they are not suspended by the filing of an appeal. However, after verifying the resolutions of the Civil Service Tribunal by which it declares null and void or founded the appeals of the sanctioned employees, it is observed that this form of execution of disciplinary sanctions affects, at least, two fundamental rights: the right to work and the right to receive remuneration. Consequently, a reflection is presented based on the analysis of the unifying vocation of Law No. 27444 and its scope of application to the administrative sanctioning procedures, including the administrative disciplinary procedure, together with guidelines for the agents involved in the disciplinary regime of the civil service regarding the important role of each one of them, with the purpose of helping to make the execution of disciplinary sanctions feasible without affecting the right to work.